2006
DOI: 10.14214/sf.341
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate and wood properties of Norway spruce cutting clones on different sites

Abstract: The effect of growth rate on weight density and strength properties of three Norway spruce cutting clones growing on three different sites in different geographic locations was studied. The purpose was to follow variation in wood physical and mechanical properties and in quality between fast-growing clones grown in environments differing in nutritional and soil properties and climate within the boreal zone. The cloned trees had been selected on grounds of good growth, health and quality. The cuttings were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
6
17
0
Order By: Relevance
“…Site variation amounted to 10% of the total variation (Tab. III), and also affected the relationship between cambial age and mean ring density, in agreement with a study by Raiskila et al (2006).…”
Section: Determinants Of Mean Ring Density In Norway Sprucesupporting
confidence: 91%
“…Site variation amounted to 10% of the total variation (Tab. III), and also affected the relationship between cambial age and mean ring density, in agreement with a study by Raiskila et al (2006).…”
Section: Determinants Of Mean Ring Density In Norway Sprucesupporting
confidence: 91%
“…The relatively stronger influence of density on MOR compared to MOE is supported by e.g. Saranpää and Repola [40] and Raiskila et al [35]. The environmental correlation between RW and density is very strong (r b = −0.93) and so is the correlations between density and both MOE and MOR (r b > 0.94).…”
Section: Correlationsmentioning
confidence: 78%
“…3b, the LWD was more variable at Kp than Dg, and trends from pith to bark for LWD were steeper (i.e., more sensitive) than other density traits. Raiskila et al (2006) also observed that the latewood components are relatively sensitive to environmental and site effects within clones of Picea abies.…”
Section: Effects Of Site Differencesmentioning
confidence: 86%